Quantification of hesperidin in citrus-based foods using a fungal diglycosidase - Mazzaferro, Laura (2012)
A simple enzymatic-spectrophotometric method for hesperidin quantification was developed by means of a specific fungal enzyme. The method utilises the diglycosidase α-rhamnosyl-β-glucosidase (EC 3.2.1.168) to quantitatively hydrolyse hesperidin to hesperetin, and the last is measured by its intrinsic absorbance in the UV range at 323 nm. The application of this method to quantify hesperidin in orange (Citrus sinensis) juices was shown to be reliable in comparison with the standard method for flavonoid quantification (high performance liquid chromatography, HPLC). The enzymatic method was found to have a limit of quantification of 1.8 μM (1.1 mg/L) hesperidin, similar to the limit usually achieved by HPLC. Moreover, it was feasible to be applied to raw juice, without sample extraction. This feature eliminated the sample pre-treatment, which is mandatory for HPLC, with the consequent reduction of the time required for the quantification.